The knowledge of the secondary schools’ students in Nowy Targ county of the cardiovascular diseases, and their prevention - Zięba, Maria; Obuchowicz, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Introduction. The spread of cardiovascular diseases related mostly to lifestyle proves that the knowledge and health awareness of society is insufficient. It also indicates the need of education of children, teenagers and adults about the issue. Health education should remind teenagers about possibilities of making pro-health choices, and due to this improve the state of health of society. Aim. The aim of the study was to learn about the knowledge of the 2nd grade secondary school students in Nowy Targ county about cardiovascular diseases and their prevention. Material and methods. Survey studies were conducted from November 2007 to June 2008 among 859 students aged 16–19 years old. The research tool was the author’s anonymous questionnaire survey. For answers to particular questions students got points according to the key. The maximum number of points that the respondent could get was 54. Log-linear analysis and multiple regression analysis were used for the purpose of statistical development, with p < 0,05 as the level of statistical significance. Results. The majority of the 2nd grade teenagers of Nowy Targ county possessed mediocre knowledge (70%) or insufficient knowledge(8%) of cardiovascular diseases and their prevention. In the same time, 41.3% of the surveyed graded their knowledge level positively, while 29% of the respondents considered it as incomplete and requiring further education about the issue. Conclusions. Factors determining a higher level of knowledge of the students surveyed about the health issues were: attending a high school, female gender and burden of disease, especially in grandparents’ generation. Place of living (town/village) had no relation to the state of health knowledge of the students. Nursing Topics 2013; 21 (1): 88–97